Plant biotechnology : recent advancements and developments - Gahlawat, Suresh Kumar. ; Salar, Raj Kumar. ; Siwach, Priyanka. ; Duhan, Joginder Singh. ; Kumar, Suresh. (Springer, 2020)
This book presents an overview of the latest advances and developments in plant biotechnology. The respective chapters explore emerging areas of plant biotechnology such as RNAi technology, fermentation technology, genetic engineering, nanoparticles and their applications, climate resilient crops, bio-films, bio-plastic, bio-remediation, flavonoids, antioxidants etc. All chapters were written by respected experts and address the latest developments in plant biotechnology that are of industrial importance, especially with regard to crop yields and post-harvest strategies. As such, the book offers a valuable guide for students, educators and researchers in all disciplines of the life sciences, agricultural sciences, medicine, and biotechnology at universities, research institutions and biotechnology companies.